1978
DOI: 10.1139/y78-157
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of ethanol in the rat brain

Abstract: The regional distribution of ethanol in selected areas of the rat brain was studied after single intravenous and intraperitoneal injections. Ethanol concentrations (measured by gas-liquid chromatography) in cortex, striatum, and hippocampus were compared with arterial and venous blood alcohol concentrations. As previously reported, equilibrium between tissue and arterial blood occurred within 3 min and followed simple diffusion kinetics. At shorter time intervals (1 min) after injection, regional ethanol conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…In these assessments, BrECs did not differ from BECs either 5 or 30 minutes after injection at any of the test ages. These results are in agreement with other reports that ethanol levels in trunk blood or retro-orbital sinus blood accurately reflect ethanol concentrations in brain as early as several minutes after administration in mice Ponomarev and Crabbe, 2002) and rats (Sunahara et al, 1978). In some studies, ontogenetic differences in ethanol distribution and metabolism have been reported.…”
Section: Discussionsupporting
confidence: 93%
“…In these assessments, BrECs did not differ from BECs either 5 or 30 minutes after injection at any of the test ages. These results are in agreement with other reports that ethanol levels in trunk blood or retro-orbital sinus blood accurately reflect ethanol concentrations in brain as early as several minutes after administration in mice Ponomarev and Crabbe, 2002) and rats (Sunahara et al, 1978). In some studies, ontogenetic differences in ethanol distribution and metabolism have been reported.…”
Section: Discussionsupporting
confidence: 93%
“…8 A). The brain experiences [EtOH] similar to that in plasma (Sunahara et al, 1978). In electrophysiological recordings, the ␦-containing extrasynaptic GABA A Rs are activated by 10 -30 mM EtOH (Wei et al, 2004;Hanchar et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, tail blood concentrations significantly underestimate systemic ethanol levels during the raising phase, while the reverse is observed when blood ethanol levels decline. Ethanol levels measured in the blood from the carotid artery or the jugular vein are better estimates of BrEC, although discrepancies between blood and brain ethanol concentrations were still observed particularly during the sharp ascending phase of blood ethanol levels (Sunahara et al 1978;Ferraro et al 1990). Generally, blood ethanol levels slightly exceeded brain ethanol levels in the first 10 min after systemic ethanol administration.…”
Section: Discussionmentioning
confidence: 99%